Pengaruh Substitusi Abu Sekam Padi Pada Semen Terhadap Kuat Lentur Beton Mutu Tinggi: The Influence Of Rice Husk Ash Substitution On Cement Regarding The Flexural Strength Of High-Strength Concrete - Murdiansyah, Lukman; Archenita, Dwina; Afriyani, Sicilia; Effendi, Effendi; Eldiswari, Zikra; Sekta, Masri Juang (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
High-strength concrete is a crucial construction material in modern infrastructure development. It involves replacing some conventional raw materials with environmentally friendly alternatives to enhance concrete quality. Rice husk ash (RHA) is an agricultural waste that contains natural pozzolanic materials capable of improving the mechanical properties and strength of concrete. The use of rice husk ash (RHA) in high-strength concrete mixtures has the potential to reduce cement consumption and enhance crack resistance. The aim of this research is to investigate the effect of substituting cement with rice husk ash and the addition of superplasticizer on the flexural strength of concrete. The target concrete strength is 4.50 MPa, with rice husk ash substitution rates of 5%, 10%, and 15% of the cement weight. This study found the flexural strength of the concrete at 28 days to be 4.71 MPa for the 5% substitution, and 3.79 MPa for both the 10% and 15% substitutions.